Image based Transesophageal Echocardiography probe tip localization - Nurullail, F. I. B. (Institute of Electrical and Electronics Engineers Inc., 2016)
Transesophageal Echocardiography (TEE) is used to visualize ultrasound heart images for diagnosis or surgery monitoring. The existing TEE is operator dependent and does not provide sufficient safety features to localize the TEE probe tip inside the human body. In order to improve safety in the usage of TEE, a novel technique for TEE probe tip localization has been developed. This technique is based on feature comparison between online TEE images retrieved from the TEE machine and an additional image database. The here presented technique includes image enhancement, segmentation, feature extraction and finally cross correlation. TEE images in a database were used as the reference for cross correlation. Test results show that the technique is able to localize the probe tip position from depth of 20 cm to 50 cm, with an accuracy of 93.2 %. This result is an approach towards the improvement of TEE safety without using additional sensors.